2022
DOI: 10.1155/2022/4704107
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effect of Family Participatory Nursing Model Based on WeChat Platform on Psychological Elasticity and Quality of Life of Patients with Lung Cancer

Abstract: Objective. To explore the effect of family participatory nursing model based on WeChat platform on psychological elasticity and life quality of patients with lung cancer. Methods. One hundred patients with lung cancer treated in our hospital from February 2019 to April 2021 were enrolled. The patients were randomly assigned into control group and study group. The control group received routine nursing and the study group received family participatory nursing model based on WeChat platform. The scores of nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…In view of the fact that at present, psychological support and psychological intervention are mostly completed by nurses and lack of professional training and guidance, the professional study and training of psychological nursing should be strengthened in the future in order to ensure the safety of patients and enhance the effect of an intervention. e same idea can be found in the study put forward by other scholars [42,43]. ey have applied new methods in the study, and the conclusions drawn can also give some support to this study.…”
Section: Discussionsupporting
confidence: 76%
“…In view of the fact that at present, psychological support and psychological intervention are mostly completed by nurses and lack of professional training and guidance, the professional study and training of psychological nursing should be strengthened in the future in order to ensure the safety of patients and enhance the effect of an intervention. e same idea can be found in the study put forward by other scholars [42,43]. ey have applied new methods in the study, and the conclusions drawn can also give some support to this study.…”
Section: Discussionsupporting
confidence: 76%
“…The related interventions mainly focused on encouragement of exercise, 39 mindfulness therapy 20 (eg, mindful breathing, mindful meditation, body scan, walking meditation, eight-sectioned exercise), relaxation training, 39 , 40 , 41 coping skills, 22 , 41 standardized health education (for both patients and their caregivers), 22 , 42 enhancement of physical care (including family care), 41 and the explanation and guide of cancer-related knowledge on WeChat platform. 43 Except for one study in which patients’ physical dimensions of burden were not significantly improved in an intervention primarily through relaxation training, 39 all the interventions in the other six studies had significant effects.…”
Section: Resultsmentioning
confidence: 96%
“…Whether the intervention can improve the emotional burden of the patients themselves deserves special attention. As shown in Table S1 , structured psychological intervention (including psychological support, health education for patients and their families, stress handling, coping skills, experience exchange, anticancer declaration learning), 22 , 34 , 41 , 42 , 44 relaxation training, 39 , 40 , 41 , 43 , 44 communication and exchange, 23 , 34 , 39 , 45 mindfulness therapy, 20 , 23 dignity enhancement and independence enhancement, 46 cognitive behavioral therapy (CBT), 21 and a nursing model intervention based on the Rosenthal effect 47 had been used to intervene the emotional burden of the patients. Structured psychological interventions, which integrated several components (such as health education, stress management, and coping skills), were beneficial in decrease of patients' emotional burden scores and could improve negative emotions (such as anxiety, depression, anger, confusion) in multiple ways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is more easy to understand and profound to master the condition of patients. 19 At the same time, nursing staff can timely understand the patients’ situation by monitoring blood glucose data upload, which is convenient for the continuity of work and the improvement of patients’ blood glucose and renal function. Xu Meifang et al 20 showed that extended nursing based on network interactive platform could significantly improve the self-efficacy and self-management behavior of patients, and reduce the levels of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%